Hummingbird (Aves: Trochilidae) assemblage using resources from the exotic African tuliptree, Spathodea campanulata (Bignoniaceae) in a Neotropical altered environment, southeastern Brazil - Pimenta,V. R. A. (2021)
Abstract The non-native African tuliptree, Spathodea campanulata (P. Beauv), is widely distributed in altered Neotropical environments, where hummingbirds are important pollinators. We investigated the assemblage of hummingbirds which fed on its nectar and described their behavior, to understand possible influences of the exotic tree on the territorial behavior in an altered environment in southeastern Brazil. Seven species fed on flower resources, mainly Eupetomena macroura (Gmelin, 1788), Amazilia lactea (Lesson, 1832), and Florisuga fusca (Vieillot, 1817). Visiting time was positive correlated with number of flowers accessed, but in most visits, hummingbirds get the nectar by pillage, instead of frontal access. Flower availability varied throughout months; however, we found no evidence of significative correlation between available flowers and number of agonistic encounters. Despite a high number of animal-plant interactions and a strong territorialism of some species observed in African tuliptree foraging site, there may be other plants at local scale influencing the behavioral patterns observed.